Antibacterial activity of Zinc Oxide Nanoparticle (ZnONP) Biosynthesis by Lactobacillus plantarium aganist pathogenic Bacteria - Zaman S. Hamza (Indian Journal of Forensic Medicine & Toxicology, 2020)
The good capability of zinc-tolerant probiotic of Lactobacillus plantarum tolerating high concentrations ofZinc+2 and producing Zinc Oxide Nanoparticles high lights the unique characteristics of these bacteria as anatural microbial cell nano-factory for a more efficient and environmentally friendly process of biosynthesisof these nanoparticles. The morphology structure and stability of the synthesized ZnO nanoparticles werestudied using structural and morphological Properties technology such as XRD and FE- SEM analysis it alsoused optical properties such as UV and FTIR spectrum. The results depicted that the synthesized nanoparticleswere moderately stable, exagonal phase, roughly spherical with maximum particles in size range within7–19nm in diameteralso this study include the antibacterial activity of the Zinc Oxide Nanoparticles on somepathogenic bacteria .It is clear in this the study that Zinc Oxide Nanoparticles has stronger inhibitory effecton pathogenic bacteria because The proposed two imaginable mechanisms for the antibacterial action ofzinc oxide nanoparticles to bacteria are first, creation of augmented levels of ROS mostly hydroxyl radicaland singlet oxygen which destruction the bacterial cell wall. Second nanoparticles deposition on bacterialsurface or nanoparticles aggregation either in the periplasm region or in the cytoplasm initiating distractionof cellular function and membranes disorganization .